Product portfolio architectural complexity and operational performance: Incorporating the roles of learning and fixed assets - Jacobs, Mark A.; Swink, Morgan (Journal of Operations Management, 2011)
AbstractManagers struggle to cope with complexity in their product portfolios. However, research into diversification, product platforms, and other issues related to product portfolio complexity has often produced inconsistent guidance. This situation is at least partially attributable to an incomplete definition of portfolio complexity, and to corresponding limitations of theories applied to date. To address these limitations, we define product portfolio complexity as a design state manifested by the multiplicity, diversity, and interrelatedness of products within the portfolio. We conceptually establish the three‐dimensional nature of complexity and present a model to provide insights into how each dimension impacts operational performance. As an extension to prior theoretical perspectives, the model explicitly addresses the roles of organizational learning and the character of fixed assets (utilization and flexibility) as mediator and moderator of product portfolio architectural complexity's effects, respectively. We also incorporate the principle of diminishing returns to address potential non‐linearities in the proposed relationships. Prior theories and research studies have neglected these issues. We conclude by discussing useful perspectives with which to view the model, and by presenting measures of portfolio complexity and approaches for testing the propositions developed herein.